Optimizing soil fertility gradients in the Enset (Ensete ventricosum) systems of the Ethiopian highlands: Trade-offs and local innovations - Amede, Tilahun; Taboge, E. (2007)
Ensete ventricosum is a perennial, security crop that feeds about 13 million people in Ethiopia. It is grown in the homesteads, covering about 18% of the farm, in mixture with Coffee, kale, and other vegetables. The recent shift from enset to cereals and continual soil fertility decline in the outfields caused food deficit for at least 3 months in a year. The objective of this work was to evaluate the effect of soil fertility gradients on enset growth, identify the major growth limiting nutrients, and identify farmers' decision making criteria in allocating resources to various enterprises. The research was conducted on farmers fields of resource rich (G1) and poor (G3) for four years (2001- 2004). Enset transplants were planted in homestead and outfields. Application of fertilizers by farmers to different units over seasons and years was recorded. Enset growth and nutrient content was measured. The results showed that the G1 group roduced about 2xs more organic waste than G3, and purchased chemical fertilizers 5xs more than the G3 farmers. About 80 % of the organic resource produced was allocated for maintaining soil fertility, while 20% being allocated as cooking fuel. Of this 65% is allocated for the enset field in the homestead. There was significantly higher N, P, K and Ca contents in the home stead soils than in the outfield, regardless of farmers' resource endowment. The P content of the outfield was the lowest, less than 25% of the P content of the homestead. Similarly organic matter in the outfield was only about 40% of the homestead. Enset plants grown in the outfields experienced about 90% height reduction and 50% reduction in pseudo stem diameter, regardless of resource categories, while the NPK content of the plant tissues grown in the outfield was significantly higher, in some case up to150% than those planted in homestead. We thus concluded that growth reduction in the outfield was not directly related to NPK deficiency, but it could have been caused by off-season moisture stress in the outfields, manifested by low soil organic matter. The attempt to attract resources to the outfield using enset as an attractant crop failed, not because of labour shortage but because of unavailability of enough organic resources in the system. Hence on spot management of nutrients was initiated by farmers.